Diagnosis of metastatic adenoid cystic carcinoma of the breast on pleural fluid cytology in a 60‐year‐old male. Issue 4 (9th October 2020) - Hogan, Keenan O.; Fan, Fang
Abstract: Adenoid cystic carcinoma (AdCC) is a rare triple‐negative breast cancer with a favorable prognosis, although cases of distant metastases have been reported. Less than 10 cases of AdCC of the breast in males have been reported. We report a unique presentation of pleural fluid metastasis diagnosed by cytologic evaluation of pleural fluid in a 60‐year‐old male patient with AdCC of the breast. Careful surveillance and cytologic evaluation of effusion specimens can detect metastases with the aid of cellblock preparations and immunohistochemical stains.